Handbook of Stillinger-Weber Potential Parameters for Two-Dimensional Atomic Crystals - Jiang, Jin-Wu; Zhou, Yu-Ping (IntechOpen, 2017)
A large number of two-dimensional atomic crystals have emerged in recent years. The interatomic potential is a fundamental ingredient for the simulation of these atomic crystals. This book provides the parameters of the Stillinger-Weber potential for 156 two-dimensional atomic crystals, which will help readers to efficiently start up their simulations.